Enhancement of CO2 biofixation and lipid production by Chlorella vulgaris using coloured polypropylene film. Issue 16 (16th July 2019) - Znad, Hussein; Al Ketife, Ahmed M.D.; Judd, Simon
ABSTRACT: Chlorella vulgaris was cultivated with light at different wavelengths ( λmax ) and irradiation intensities ( I ) by applying a coloured tape (CT) as a simple, inexpensive light filter. C. vulgaris was cultivated in a standard medium using blue (CTB ), green (CTG ), red (CTR ), yellow (CTY ) and white (CTW ) CT to filter the light, as well the unfiltered light (U). The influence of λmax and I on specific growth rate ( μ ), nutrient removal efficiency (% RE of total nitrogen, TN, and phosphorus, TP), CO2 fixation rate ( RC ) and lipid productivity ( Plipid ) were evaluated. The highest biomass concentration Xmax of 2.26 g L −1 was measured for CTW with corresponding μ, TN and TP RE, RC and Plipid values of 0.95 d −1, 92% and 100%, 0.67 g L −1 d −1 and 83.6 mg L −1 d −1, respectively. The normalised μ and Plipid for U were significantly lower than in CTW of 33–50% and 75%, respectively. The corresponding non-normalised parameter values for CTB were significantly lower at 0.45 d −1, 0.18 g L −1, 15% and 37%, 0.03 g L −1 d −1 and 1.2 mg L −1 d −1 . Results suggest a significant impact of I and λmax, with up to a 50% increase in growth and nutrient RE from optimising these parameters.